Phase transitions and He bubble evolution under sequential He ions implantation and Fe ions irradiation: New insight into the irradiation resistant of Ti3AlC2. Issue 16 (December 2022) - Pang, Lilong; Tai, Pengfei; Zhang, Linqi; Niu, Lijuan; Wang, Zhiguang; Chang, Hailong; Shen, Tielong; Cui, Minghuan; Huang, Sihao; Qi, Le; Gao, Xing; Wei, Kongfang; et al.
Abstract: The phase transitions and He bubble evolution in Ti3 AlC2 with the sequential He ions implantation and Fe ions irradiation at room temperature were investigated with grazing incidence X-ray diffraction and transmission electron microscopy. The pre-implanted He makes an obviously effect of suppressing the phase transitions caused by the following Fe ions irradiation. The following Fe ions irradiation was also found to create a competitive effect on the evolution of the pre-formed He bubbles. It can cause not only the growth of He bubbles, but the shrinkage (or re-solution of He bubbles). This will improve the resistance to He bubbles induced damage for Ti3 AlC2 . Both He ions implantation and Fe ions irradiation actually inhibit each other's irradiation damage to the material. This may play a positive role in reducing irradiation damage to the Ti3 AlC2 material, and also provides new insight into irradiation resistance of this material.